Pre‐bariatric surgery acute kidney injury: Can this be prevented? - Natnicha Leelaviwat; Pitchaporn Yingchoncharoen; Jerapas Thongpiya; Mahmoud Abdelnabi; Poemlarp Mekraksakit (Clinical Case Reports, 2023)
Key Clinical Message Pre‐bariatric surgery dietary recommendations should take into account daily protein intake and other risk factors for kidney injury. This is important because a high protein intake can potentially lead to kidney injury. Abstract Bariatric surgery has been shown to be a highly effective intervention for achieving weight loss and reducing obesity related‐comorbidities. Acute kidney injury (AKI) is considered one of the common complications in perioperative and post‐bariatric surgery. However, pre‐bariatric surgery AKI has never been reported. Several studies demonstrated that pre‐bariatric surgery weight loss improved surgical outcomes and decrease postoperative complications. Some diet regimens have been introduced including low‐caloric diet (LCD), very‐low caloric diet (VLCD), and very‐low caloric ketogenic diet (VLCKD). We present a patient who develops AKI after 10 days of having a high‐protein diet from a pre‐bariatric weight loss strategy.